THE EFFECT OF INSTITUTIONAL OWNERSHIP, MANAGERIAL OWNERSHIP, PUBLIC OWNERSHIP ON ENVIRONMENTAL PERFORMANCE WITH PROFITABILITY AS A MODERATING VARIABLE - Novianti, Nur Ana Eka; Waharini, M.Si, Faqiatul Mariya (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
Shareholders really think about the strategy that should be used to start investing their shares in a company. One of them is by tending to invest in companies that have high concern for the environment and good social insight towards society. This study aims to empirically examine the effect of institutional ownership, managerial ownership and public ownership on environmental performance. The moderating variable used is profitability. Environmental performance proxies use PROPER (company assessment in managing the environment). The sample used is a company listed on the Jakarta Islamic Index for 2018-2022. Sampling using purposive sampling technique. The number of samples in this study were 9 companies with a total of 45 observations. Test the hypothesis using multiple linear regression analysis. The results of the research show that institutional ownership has a negative effect on environmental performance. Meanwhile, managerial ownership and public ownership have no effect on environmental performance. Profitability is able to moderate the effect of managerial ownership and public ownership on environmental performance.